READING INSTRUCTION IN UNDER GRADUATE ENGLISH PROGRAM - Besral, Besral (English Department FBS UNP, 2008)
Having lack of motivation and low intelligence have often been considered as sources of students' failures in Reading Subject. Such this unfair judgement on the parts of the lecturers remains in its existence in many colleges and universities although dozens of approaches and methodologies have long exalted through Communicative Language Teaching principles. The current study tries to elaborate some interrelated factors that influenced students' achievement in Reading Instruction at the English Tadris Department. Clear vision as reflected in the planning and instructional program is considered to be the primary importance to accomplish successful teaching.Some basic theoretical frameworks as well as the most current trends in our educational practices are presented to picture students' progress. Finally, with a more interactive classes depicted to upgrade students' imaginations, the writer comes to the conclusion that students' success in reading depends largely on how the teacher/ instructor play his/her roles as a manager,a motivator, a supervisor, and as a teacher